2011
DOI: 10.1068/a43570
|View full text |Cite
|
Sign up to set email alerts
|

Land Use, Transport, and Carbon Futures: The Impact of Spatial Form Strategies in Three UK Urban Regions

Abstract: Land-use and transport systems are an important determinant of carbon dioxide emissions from urban regions. It is often asserted that urban compaction is the spatial policy best able to constrain travel and emissions, but evidence supporting this assertion is limited, particularly with respect to the combined emission from transport and land use. Here, using land-use -transport interaction models, a residential dwelling type model, and transport and emission models, we forecast and assess carbon dioxide emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…However, high heterogeneity in terms of geographic and climatic factors makes it difficult to generalise (e.g., Mitchell, Hargreaves, Namdeo, & Echenique, 2011). For instance, Kahn (2000) found no significant differences in residential energy use between suburban areas and centres.…”
Section: Housingmentioning
confidence: 95%
“…However, high heterogeneity in terms of geographic and climatic factors makes it difficult to generalise (e.g., Mitchell, Hargreaves, Namdeo, & Echenique, 2011). For instance, Kahn (2000) found no significant differences in residential energy use between suburban areas and centres.…”
Section: Housingmentioning
confidence: 95%
“…This is due to the fact that there is a clear link between land use and transport demand, and therefore, there is a need to issue planning guidance that aims to limit the traffic generation potential of new development (Sorrell 1992). For example, unlike greenfieldbased development in the UK, the land use policy has been reinforced in the last decade with a substantial increase in the share of dwellings built on brownfield land (from 54 % in 1996 to 72 % in 2006), and density of new dwellings-i.e., 25 to 41 dwellings per hectare over the same period (Mitchell et al 2011). In a study in the Netherlands, Grazi et al (2008) found that locations where density is 500 addresses per square kilometer higher, CO 2 emissions from transport are on average 15 % lower.…”
Section: Co 2 Emission Reduction: Technological Efficiency Versus Behmentioning
confidence: 99%
“…Other researchers that have focused on the relationship between urban densities and travel have found similar outcomes, albeit to varying degrees (Cao, Mokhtarian, & Handy, ; Mitchell, Hargreaves, Namdeo, & Echenique, ; Yang, French, Holt, & Zhang, ). For instance, Robert Cervero, who explored the relationship between urban environments and public transit use, argued that for every 10% increases in population and employment densities, transit ridership increased between 5% and 8% (Cervero, , p. 72).…”
Section: Literature Review: the Built Environment And Travel Behaviormentioning
confidence: 76%